how do i solve this?

x(1+2x)= (2x-1)(x-2)

2 answers

multiply out both sides. Then, gather like terms into quadratic form.

ax^2 +bx +c=0

Then, factor, or use the quadratic formula.
what does it mean to multiply out both sides
Similar Questions
  1. Combine like terms:-3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x: 8x-11= -11x+18 Solve for x: -2(x-5)+7=z-8-5x Solve for x: (x-2)/5 -
    1. answers icon 8 answers
  2. Solve the indicated variable:1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32
    1. answers icon 1 answer
  3. Put in the correct orderSolve exponentiation. Solve multiplication and division. Solve operations within parentheses Solve
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions